Acute thoracic aortic dissection (Stanford B): challenges in early detection and management - Abdullah, Noraini Sarina; Ahmad Saad, Fathinul Fikri (OMICS International, 2015)
Background: Diagnosis of acute thoracic dissection is crucial given its potential fatal complications in delayed treatment response. Early and appropriate intervention renders obviation of futile surgery. Case report: A 63 years old man with uncontrolled hypertension who presented to emergency department with sharp excruciating chest pain which radiated to the back. A Computed Tomography Angiography (CTA) was done which confirmed thoracic aortic dissection (Stanford type B) (Figures 1 and 2). An uneventful endovascular stent graft with Captivia system was done to contain the entry tear. The patient was doing well post procedure with well-controlled blood pressure. Conclusion: This case reports documents challenges in making immediate diagnosis of acute aortic dissection and in providing appropriate intervention to avert fatal outcomes.